OVER EXPLOITATION OF MEDICINAL PLANTS A SET BACK TO GENE POOL: Life Science-Botany - MOHAMMED, M.SILAR; KUMAR, B.VINAY (International Journal of Life Science and Pharma Research, 2012)
Medicinal plants are the chief source of active compounds for drugs to cure diseases of human beings and his live stock. Presence of these plants in abundance in an area is a gift from god for positive approaches in the preparation of medicine and maintenance of plant diversity. It is the responsibility of all in general and scientists in particular to save the population of these plants by conservational measures when these are subjected to threat of higher level and over exploitation by people for their selfish needs .It is practically observed in Kurnool district at Mahanandi that the two medicinal plants are being exploited by people living near vicinity of the forest. Hence there is an urgent need to educate, to conserve, and to maintain the gene pool before being lost and becomes the threatened category